Does the sensitivity of Southern Ocean circulation depend upon bathymetric details? - Hogg, A; Munday, D (Royal Society of London, 2014)
The response of the major ocean currents to changes in wind stress forcing is investigated with a series of idealized, but eddy-permitting, model simulations. Previously, ostensibly similar models have shown considerable variation in the oceanic response to changing wind stress forcing. Here, it is shown that a major reason for these differences in model sensitivity is subtle modification of the idealized bathymetry. The key bathymetric parameter is the extent to which the strong eddy field generated in the circumpolar current can interact with the bottom water formation process. The addition of an embayment, which insulates bottom water formation from meridional eddy fluxes, acts to stabilize the deep ocean density and enhances the sensitivity of the circumpolar current. The degree of interaction between Southern Ocean eddies and Antarctic shelf processes may thereby control the sensitivity of the Southern Ocean to change.